Does Diabetes Mellitus Increase the Short- and Long-Term Mortality in Patients With Critical Acute Myocardial Infarction? Results From American MIMIC-III and Chinese CIN Cohorts - Chen, Shiqun; Huang, Zhidong; Chen, Liling; Zhao, Xiaoli; Kang, Yu; Lai, Wenguang; Lu, Xiaozhao; Zhou, Yang; He, Yibo; Huang, Haozhang; Li, Qiang; Liu, Jin; et al. (Frontiers in Endocrinology, 2021)
Background: The harmful effect of diabetes mellitus (DM) on mortality in patients with acute myocardial infarction (AMI) remains controversial. Furthermore, few studies focused on critical AMI patients. We aimed to address whether DM increases short- and long-term mortality in this specific population. Methods: We analyzed AMI patients admitted into coronary care unit (CCU) with follow-up of ≥1 year from two cohorts (MIMIC-III, Medical Information Mart for Intensive Care III; CIN, Cardiorenal ImprovemeNt Registry) in the United States and China. Main outcome was mortality at 30-day and 1-year following hospitalization. Kaplan-Meier curves and Cox proportional hazards models were constructed to examine the impact of DM on mortality in critical AMI patients. Results: 1774 critical AMI patients (mean age 69.3±14.3 years, 46.1% had DM) were included from MIMIC-III and 3380 from the CIN cohort (mean age 62.2±12.2 years, 29.3% had DM). In both cohorts, DM group was older and more prevalent in cardio-renal dysfunction than non-DM group. Controlling for confounders, DM group has a significantly higher 30-day mortality (adjusted odds ratio (aOR) [95% CI]: 2.71 [1.99-3.73] in MIMIC-III; aOR [95% CI]: 9.89 [5.81-17.87] in CIN), and increased 1-year mortality (adjusted hazard ratio (aHR) [95% CI]: 1.91 [1.56-2.35] in MIMIC-III; aHR [95% CI]: 2.62[1.99-3.45] in CIN) than non-DM group. Conclusions: Taking into account cardio-renal function, critical AMI patients with DM have a higher 30-day mortality and 1-year mortality than non-DM group in both cohorts. Further studies on prevention and management strategies for DM are needed for this population.